The role of the unit sister - emphasis on quality of care and accountability - R. Bergman (AOSIS, 1982)
The subject of this paper includes three important concepts. They are: role of the unit sister (or head nurse), quality of care and accountability. Each of these will be dealt with briefly and an attempt made to show the interrelationship between them.